Nutrition of background forest species of migratory passerine birds during the early-spring period - Domantsevich, Dmitry G. (Experimental Biology and Biotechnology, 2018)
In this work the food content of four background forestry migratory passerine birds of Belarus: Chaffinch (Fringilla coelebs), Robin (Erithacus rubecula), Blackbird and Song trush (Turdus merula, Turdus philomelos) in conditions of the early-spring period is analyzed. The work is based on the results of digestive tracts contents analysis of birds that died during the period from 2010 to 2015 from the last ten-day period of March to the last ten-day period of April in different regions of the country. Totally 919 food items were found in the digestive tracts of studied species of birds. In Chaffinch nutrition it is noted a high occurrence and proportion of weevils (Curculionoidae). In Robin nutrition − the presence of invertebrates of different ecological groups and the complete absence of plant foods. The consumption of coniferous trees seeds on the territory of Belarus in the early spring by Blackbirds and Song trushes is notes, that is reported in the literature for the first time. For Chaffinches, Robins and Blackbirds some general patterns in the consumption of animal feeds have been revealed: more than 50 % of all food objects in their diet are insects, of which more than half are coleopterans of different taxonomic and ecological groups.